The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep32578
|View full text |Cite
|
Sign up to set email alerts
|

Li-ion Battery Separators, Mechanical Integrity and Failure Mechanisms Leading to Soft and Hard Internal Shorts

Abstract: Separator integrity is an important factor in preventing internal short circuit in lithium-ion batteries. Local penetration tests (nail or conical punch) often produce presumably sporadic results, where in exactly similar cell and test set-ups one cell goes to thermal runaway while the other shows minimal reactions. We conducted an experimental study of the separators under mechanical loading, and discovered two distinct deformation and failure mechanisms, which could explain the difference in short circuit ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 23 publications
7
95
0
Order By: Relevance
“…This point was the initiation of separator thinning and anode decoating. This finding corroborated reports of Zhang et al on separator failure modes and inflection point under biaxial loading [30]. This local damage to anode and separator before the onset of short circuit can explain the decrease in cell stiffness in the Stage II observed in uninterrupted tests.…”
Section: Pouched Cellssupporting
confidence: 81%
See 2 more Smart Citations
“…This point was the initiation of separator thinning and anode decoating. This finding corroborated reports of Zhang et al on separator failure modes and inflection point under biaxial loading [30]. This local damage to anode and separator before the onset of short circuit can explain the decrease in cell stiffness in the Stage II observed in uninterrupted tests.…”
Section: Pouched Cellssupporting
confidence: 81%
“…Onset of short circuit was identified by a drop in voltage in case of live cells which coincides with peak force. Two failure modes were observed which were explained by the soft and hard internal short circuit theory for separators [30]. The results suggested that the occurrence of soft short circuit may not be easily detected at higher impact velocities.…”
Section: Elliptical Cellsmentioning
confidence: 82%
See 1 more Smart Citation
“…[10][11][12][13][14][15] Mechanical properties of fresh cells and components have been used to develop nite element models for the battery cells. When batteries are used in automotive applications, an understanding of mechanical properties are essential to manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…The separator is usually made of porous polyethylene or polypropylene, with the thickness in the range of 10-30 μm [11]. If the electrode stack is crushed or penetrated through, rupture of the separator would result in direct contact between cathode and anode, forming an internal short circuit (ISC).…”
Section: Introductionmentioning
confidence: 99%